2018
DOI: 10.1155/2018/4607945
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Alginate-Chitosan Hollow Nanospheres for Codelivery of Doxorubicin and Paclitaxel for the Effect of Human Lung Cancer A549 Cells

Abstract: A biodegradable alginate coated chitosan hollow nanosphere (ACHN) was prepared by a hard template method and used for codelivery of doxorubicin (DOX) and paclitaxel (PTX) to investigate the effect on human lung cancer A549 cells. PTX was loaded into the nanometer hollow structure of ACHN through adsorption method. DOX was coated on surface of ACHN through electrostatic interaction. Drug release studies exhibited a sustained-release effect. According to X-ray diffraction patterns (XRD), differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The EE and LE of the nanospheres were determined (Yang et al, 2017). The nanospheres were characterized using FTIR (Abbas et al, 2018;Dong et al, 2018), electron microscopy (Shi et al, 2016;Nantachit et al, 2017;Tao et al, 2018), and laser particle size analysis (Couvreur et al, 2002;Zhang et al, 2015;Shi et al, 2016;Ahmad et al, 2018;Panchu et al, 2018;von Halling Laier et al, 2018). The results showed that C-PC/CMC-CD55sp nanospheres were successfully constructed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EE and LE of the nanospheres were determined (Yang et al, 2017). The nanospheres were characterized using FTIR (Abbas et al, 2018;Dong et al, 2018), electron microscopy (Shi et al, 2016;Nantachit et al, 2017;Tao et al, 2018), and laser particle size analysis (Couvreur et al, 2002;Zhang et al, 2015;Shi et al, 2016;Ahmad et al, 2018;Panchu et al, 2018;von Halling Laier et al, 2018). The results showed that C-PC/CMC-CD55sp nanospheres were successfully constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Encapsulation Efficiency (EE) and Loading Efficiency (LE) of C-PC in nanospheres were calculated as follows (Yang et al, 2017): EE = weight of C − PC in the nanospheres initial weight of C − PC  100 % LE = weight of C − PC in the nanospheres weight of the nanospheres  100 % Nanospheres were evaluated using FTIR spectra across the range of 500-4,000 cm -1 (Abbas et al, 2018;Dong et al, 2018). Nanospheres morphology was observed using a transmission electron microscope (Shi et al, 2016;Nantachit et al, 2017;Tao et al, 2018). Zeta potential (surface charge) and particle size (nanospheres size) were measured using a laser particle size analyzer at 25°C (Zhang et al, 2015;Ahmad et al, 2018;Panchu et al, 2018;von Halling Laier et al, 2018).…”
Section: Synthesis Of C-pc/cmc-cd55sp Nanospheresmentioning
confidence: 99%
“… Nil Co-delivery of paclitaxel and doxorubicin can effectively inhibit cell proliferation and promote cell apoptosis due to the nanoscale effect of particles and the synergistic effect of combined drugs. ( Tao et al, 2018 ) F10 A hybrid system composed of multi-walled carbon nanotubes (MWCNT) coated with chitosan is produced as a pH-responsive carrier of methotrexate. MWCNT are synthesized by fixed-bed chemical vapour deposition method.…”
Section: Lung Cancer and The Applications Of Chitosan Based Carriersmentioning
confidence: 99%
“…The cytotoxic effects of chitosan are characterized by apoptosis via the activation of caspase 3 and caspase 8 ( Almutairi et al, 2019 ; Bharathi et al, 2019 ). The development of chitosan as pulmonary drug delivery carrier and as conjugate backbone of lung cancer therapy has been widely explored and gained successful outcomes ( Bharathi et al, 2019 ; Chi et al, 2019 ; Cirillo et al, 2019 ; Li et al, 2019 ; Pandey et al, 2019 ; Tao et al, 2018 ; Wang et al, 2017 ). The chitosan based pulmonary drug delivery carrier has been shown to reduce systemic toxicity of anti-cancer drugs, increase drug bioavailability in lungs and improve anti-tumor efficacy of the drugs.…”
Section: Lung Cancer and The Applications Of Chitosan Based Carriersmentioning
confidence: 99%
“…Alginate‐coated chitosan hollow nanosphere showed any toxicity and exhibited a sustained‐release effect according to differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT‐IR) analysis, and X‐ray diffraction patterns (XRD). Their results indicated that alginate‐coated chitosan hollow nanosphere can be applied for transport multiple drugs in combination therapy …”
Section: Chitosanmentioning
confidence: 99%